Progeny Variation in Seed, Germination and Seedling Traits in Seedling Seed Orchard of Pongamia pinnata (L.) Pierre - Rahangdale, C. P.; Kosht, L. D.; Jain, K. K.; Dongre, R. P. (Indian Forester, 2015)
22 progenies of seedling seed orchard of Pongamia pinnata were evaluated for seed morphomatric traits, germination traits and seedling at the age of 8 year old provenance trial. Patterns of genetic variation in Pongamia pinnata (L.) Pierre, a humid tropical oilseed leguminous tree, were evaluated at the population level. Analysis of variance revealed significant differences among progenies in all studied attributes at nursery stage. All seed morphometric traits were positively correlated among themselves and with germination traits viz., germination per cent, germination value and germination index, except days of initiation of germination and germination energy but no significant correlation was observed with seedling growth traits at nursery stage. The genetic parameters for seed morphometric traits, germination and seedling growth also showed a wide range of variations. Heritability value for different traits was varied from 79 to 96% for seed morphometric traits, 63-84% for germination traits, 83% for shoot height and 62% for volume index and 56% for collar diameter. Seed weight and seed volume showed high heritability value coupled with more genetic gain, which indicate the presence of good amount of heritable additive component in both traits.